The commitment to act for oral health and happiness - Estela de los Ángeles Gispert Abreu; María Rosa Salas Adam (Editorial Ciencias Médicas, 2020)
Oral health and happiness require social action. The good health is one of the main determinants of happiness, since it produces joy and is usually expressed through a smile or laughter that could be inhibited by oral conditions. The International Dental Federation's "United for Oral Health" Campaign in 2020 aims to make commitments for decision-makers, professionals and the population to reduce the global burden of oral diseases. Establishing commitments and consequent actions can contribute to improvements in oral health, making it necessary to establish systematic actions. In the Cuban context, it is a strength that the stomatology strategy is national and has a public health focus, although it is necessary to reinforce the monitoring and evaluation of the impact of the actions, stimulate creativity, dialogue communication, and review which commitments they must be consolidated to contribute to oral health and therefore to happiness."